Henry James across Borders - Thomas Constantinesco (Viatica)
This essay explores the opposition between the figures of the cosmopolitan and the patriot in a selection of James’s letters and travel writings. It focuses on the crossing of borders as revelatory of the mutual haunting of the “native” and the “alien.” But crossing the frontier also entails encountering the representatives of State violence. Through James’s mise en scène of his ambivalent fascination for the martial figure of the soldier, the frontier becomes a critical locus for the queering of identities and affiliations.